Misconceptions of primary school students about the subject of fractions: views of primary teachers and primary pre-service teachers - Yasemin Deringöl (International Journal of Evaluation and Research in Education (IJERE), 2019)
This study was conducted with the aim of investigating the current knowledge of Primary Teachers and Primary Pre-service Teachers on the misconceptions of primary school students about the subject of fractions. The qualitative research method of case study was used to conduct the research. The data were collected with semi-structured forms that were developed by the researcher to collect the views of Primary Teachers and Primary Pre-service Teachers on the topic. The participants stated that, regarding the subject of fractions, primary school students had difficulties the most in representing fractions by models, the concepts of denominator and numerator, when they need to rank fractions, when they need to solve problems, reading and writing concepts that express fractions, distinguishing types of fractions – converting these, showing a given fraction on number lines and operations on fractions, and they had misconceptions about these.